2005
DOI: 10.1128/aac.49.8.3239-3250.2005
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Antibacterial Activities of CS-023 (RO4908463), a Novel Parenteral Carbapenem

Abstract: CS-023 (RO4908463, formerly R-115685) is a novel 1␤-methylcarbapenem with 5-substituted pyrrolidin-3-ylthio groups, including an amidine moiety at the C-2 position. Its antibacterial activity was tested against 1,214 clinical isolates of 32 species and was compared with those of imipenem, meropenem, ceftazidime, ceftriaxone, ampicillin, amikacin, and levofloxacin. CS-023 exhibited a broad spectrum of activity against gram-positive and -negative aerobes and anaerobes, including methicillin-resistant Staphylococ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
39
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 16 publications
(12 reference statements)
1
39
0
Order By: Relevance
“…Treatment guidelines for these infections recommend specific antibiotics or combinations of antibiotics against these pathogens (1,28). Of all the ␤-lactams, carbapenems have the broadest spectra of antibacterial activity; tomopenem (formerly CS-023), a novel 1␤-methylcarbapenem, exhibits activity against diverse hospital pathogens, including MRSA and P. aeruginosa isolated in the United States and Japan (9,33). In a previous clinical trial in healthy volunteers, tomopenem (27) showed a longer half-life (1.7 h) than imipenem (IPM)-cilastatin (1.0 h) (22) and meropenem (MEM) (0.9 h) (26).…”
mentioning
confidence: 99%
“…Treatment guidelines for these infections recommend specific antibiotics or combinations of antibiotics against these pathogens (1,28). Of all the ␤-lactams, carbapenems have the broadest spectra of antibacterial activity; tomopenem (formerly CS-023), a novel 1␤-methylcarbapenem, exhibits activity against diverse hospital pathogens, including MRSA and P. aeruginosa isolated in the United States and Japan (9,33). In a previous clinical trial in healthy volunteers, tomopenem (27) showed a longer half-life (1.7 h) than imipenem (IPM)-cilastatin (1.0 h) (22) and meropenem (MEM) (0.9 h) (26).…”
mentioning
confidence: 99%
“…The MIC 50 and MIC 90 against methicillin-sensitive S. aureus (MSSA) are 0.12 and 0.12 to 0.25 mg/liter (17,19,32). For methicillin-resistant S. aureus (MRSA), the MIC 50 and MIC 90 are 2 and 4 to 16 mg/liter (17,19,32). This contrasts to imipenem and meropenem, which have MRSA MIC 90 values of 32 and 16 to 32 mg/liter.…”
mentioning
confidence: 99%
“…Tomopenem retains in vitro potency against extended-spectrum ␤-lactamase-producing Escherichia coli and Klebsiella spp. as well as Pseudomonas aeruginosa (8,17,19,33).The pharmacokinetics studies with male healthy volunteers indicate relatively typical carbapenem pharmacokinetics except for a prolonged serum half-life of about 2 h, which is related to a lack of renal tubular secretion (29). Tomopenem is stable to digestion by human renal DHP-1 (18) and produces peak serum concentrations of about 44 mg/liter after a 700-mg dose and 100 mg/liter after a 1,400-mg dose in humans (29).…”
mentioning
confidence: 99%
See 2 more Smart Citations